Comparative studies of glial fibrillary acidic protein and brain‐derived neurotrophic factor expression in two transgenic mouse models of Alzheimer's disease. (17th July 2020) - Edwards, Stephen R.; Khan, Nemat; Coulson, Elizabeth J.; Smith, Maree T.
Abstract: In Alzheimer's disease (AD) glial fibrillary acidic protein (GFAP) is expressed by reactive astrocytes surrounding β‐amyloid (Aβ) plaques, whereas brain‐derived neurotrophic factor (BDNF) levels are typically reduced. We compared the expression of GFAP, BDNF, and its precursor proBDNF in the dorsal hippocampus of two transgenic AD mouse models. APPSwe YAC mice expressing the APPSwe transgene on a yeast artificial chromosome (YAC) were assessed at age 4 and 21 months, and APPSwe/PS1dE9 mice co‐expressing mutant amyloid precursor protein (APPSwe) and presenilin‐1 (PS1dE9) were assessed at age 4 and 9 months. Significantly increased (1.4‐fold) GFAP expression was observed in APPSwe YAC c.f . wild‐type (Wt) mice aged 21 months, when Aβ deposition was first evident in these mice. In APPSwe/PS1dE9 mice aged 4 and 9 months, GFAP expression was significantly increased (1.6‐ and 3.1‐fold, respectively) c.f. Wt mice, and was associated with robust Aβ deposition at 9 months. BDNF expression was significantly lower in 4‐ and 21‐month old APPSwe YAC mice (0.8‐ and 0.6‐fold, respectively) c.f. age‐matched Wt mice, whereas proBDNF expression was significantly higher (10‐fold) in the APPSwe YAC c.f. Wt mice aged 21 months. In APPSwe/PS1dE9 mice aged 4 months, BDNF expression was significantly lower (0.4‐fold) c.f . age‐matched Wt mice and was equivalent to that in 9‐month old mice of both genotypes; proBDNF expression mirrored that of BDNF in this strain. These findings support a role for reactive astrocytes and neuroinflammation, rather than BDNF, in the spatial memory deficits previously reported for APPSwe YAC and APPSwe/PS1dE9 mice.